Life of Charles Blacker Vignoles, F.R.S., F.R.A.S., M.R.I.A. soldier and civil engineer, formerly lieutenant in H.M. 1st Royals, past-president of Institution of Civil Engineers : a reminiscence of early railway history - Vignoles, Olinthus J. 1829-1907 (Longmans, Green, and Co., 1889)
This memoir of the life and work of the late Mr C.B. Vignoles is in three sections: his life of adventure as an officer in the British Army; his work as one of the small group of civil engineers engaged in the construction of the earliest railways in England and Ireland; and his foreign engineering work.